A Study on the Measure for Improving the Website of ScienceON - noh, younghee (International Journal of Knowledge Content Development & Technology, 2024)
This study was conducted for the purpose of deriving the existing ScienceON elements and reorganizing them to increase user convenience and utilization. Towards this end, implications were derived by analyzing the current status of the ScienceON’s website, case studies and analysis of major similar institution websites, and user satisfaction surveys. Based on the derived contents, key terms were analyzed and redefined, the menu system was reorganized, and the menu names were redefined, and the menu system was reorganized to match the direction and identity of the redefined ScienceON. The study results based on such are as follows. First, the ScienceON’s brand selection criteria and direction were based on service sustainability, service inclusiveness, recognition of portal characteristics, user friendliness and intuitiveness. Considering the meaning of branding, branding strategy, and selection criteria for ScienceON branding, ScienceON, Ontong ScienceON, ScienceONPlatform, science information portal, ScienceON, Mecca of science and technology information, and 5 brand names such as ScienceON were proposed. Second, to improve accessibility, usability, and satisfaction, it would be necessary to redefine current terms. Towards this end, it would be necessary to change the terminology of knowledge infrastructure search and to unify and organize the terminology. Third, in the current menu, the services provided as analysis services and curation services are organized in the beta service menu, and data such as papers, patents, reports, and trends are also serviced only through integrated search, and hence, each data type and service type classification must be improved.